C and Data Structures by Practice - Vasappanavara, Ramesh (New Age International, 2011)
This book on C & Data Structures by Practice offers contemporary and comprehensive introduction to C language and data structures. It provides indepth coverage of all the concepts of the C language and data structure with an emphasis on problem solving approach. The underlying theory has been explained with the examples so that student can be at ease.